1999
DOI: 10.1002/(sici)1099-1085(199901)13:1<1::aid-hyp674>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The particle size characteristics of fine-grained channel deposits in the River Exe Basin, Devon, UK

Abstract: Abstract:Deposition and storage of ®ne-grained (562 . 5 mm) sediment in the hyporheic zone of gravel bed rivers frequently represents an important cause of aquatic habitat degradation. The particle size characteristics of such ®ne-grained bed sediment (FGBS) exert an important control on its hydrodynamic properties and environmental impact. Traditionally, particle size analysis of FGBS in gravel bed rivers has focused on the absolute size distribution of the chemically dispersed mineral fraction. However, rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…It clearly shows the shift in size with the median size of the flocculated sediment lying between 20 and 80 mm compared with an absolute value of about 5 mm. Phillips and Walling (1999) also show a seasonal variation in particle size, with the size of flocculated particles being higher in the summer when biological activity is greatest but with the absolute particle size being higher in winter when erosion is more active.…”
Section: The Nature Of Fine Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…It clearly shows the shift in size with the median size of the flocculated sediment lying between 20 and 80 mm compared with an absolute value of about 5 mm. Phillips and Walling (1999) also show a seasonal variation in particle size, with the size of flocculated particles being higher in the summer when biological activity is greatest but with the absolute particle size being higher in winter when erosion is more active.…”
Section: The Nature Of Fine Sedimentmentioning
confidence: 99%
“…Grain sizes between 1 and 2.6 mm are entirely incorporated into flocs (Droppo and Ongley, 1992). Figure 10.4b shows example distributions of both effective particle size and absolute (disaggregated) particle size for both suspended sediment and bed sediments taken from Phillips and Walling (1999). It clearly shows the shift in size with the median size of the flocculated sediment lying between 20 and 80 mm compared with an absolute value of about 5 mm.…”
Section: The Nature Of Fine Sedimentmentioning
confidence: 99%
“…Sediment particle-size properties, recorded to describe conditions experienced by the macrofauna, should therefore preferably be recorded in situ [45,46]. Depth, which was not strongly correlated with any other variable in Subset-, was the only variable strongly correlated with the main coenocline in that subset.…”
Section: Ecoclines Related To the Main Coenocline (Dca1)mentioning
confidence: 99%
“…These data of particle size are mostly obtained after fully dispersing the sediment into primary mineral particles (Slattery and Burt 1997), which, as a traditional sizing technique, provides a consistent baseline for evaluating the spatial and temporal variability of sediment size (Droppo and Ongley 1994;Walling et al 2000). However, recent work has indicated that much of sediment is eroded in aggregated form and the dispersed sediment-size distribution is of limited value in studying sediment movement (Walling 1990;Phillips and Walling 1999;Martínez-Mena et al 1999). In contrast, the particle-size distribution analyzed without chemical dispersion reflects the size composition of the sediment when eroded and serves as a better indicator for sediment transport behavior (Slattery and Burt 1997;Walling et al 2000).…”
Section: Introductionmentioning
confidence: 99%